THE EFFECT OF MANAGERIAL OWNERSHIP ON EARNINGS MANAGEMENT WITH CAPITAL STRUCTURE AS A MEDIATING VARIABLE (AN EMPIRICAL STUDY ON MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE IN 2022–2024) (Proceeding of SINERGY, 2026)
This study investigates the relationship between managerial ownership and earnings management and examines whether capital structure functions as a mediating mechanism in this relationship. The motivation for this research arises from inconsistent empirical evidence regarding the effectiveness of managerial ownership as a corporate governance tool in constraining opportunistic earnings management practices. Drawing on Agency Theory, this study focuses on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2022–2024 period. An empirical quantitative approach is employed using secondary data obtained from audited annual financial reports. The final sample comprises 231 firm-year observations selected through purposive sampling. Multiple linear regression analysis is applied, accompanied by mediation testing using a stepwise regression procedure. Earnings management is measured using discretionary accruals based on the Modified Jones Model, managerial ownership is proxied by the proportion of shares held by management, and capital structure is represented by the Debt to Asset Ratio. The findings indicate that managerial ownership does not exhibit a statistically significant relationship with earnings management. In addition, managerial ownership is not significantly associated with capital structure, and capital structure does not significantly influence earnings management. Consequently, capital structure does not mediate the relationship between managerial ownership and earnings management. These results suggest that ownership-based governance mechanisms and financing policies may not operate effectively in limiting earnings management within the observed firms. This study contributes to the literature by highlighting the contextual nature of governance mechanisms derived from Agency Theory. The findings are expected to provide insights for corporate management, investors, and regulators in strengthening corporate governance and financial oversight practices.